2011
DOI: 10.1007/s13239-011-0073-3
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Aortic Flow Patterns Before and After Transcatheter Aortic Valve Implantation

Abstract: Little is known of the likely changes in blood flow velocity profiles and aortic wall shear stress (WSS) following transcatheter aortic valve implantation (TAVI). The objective of this study was to investigate the effects of TAVI on flow patterns in the thoracic aorta by using cardiovascular magnetic resonance imaging (CMR) and computational fluid dynamics (CFD). An elderly patient with aortic stenosis was examined using MRI pre-and post-TAVI, and CFD simulations were carried out incorporating MRI-derived pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 41 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…These OBCs were commonly used in previous studies (e.g. Tan et al, 2012;Cheng et al, 2016). For OBC5, zero-pressure was imposed at all the model outlets, representing the simplest outlet boundary condition.…”
Section: Discussionmentioning
confidence: 99%
“…These OBCs were commonly used in previous studies (e.g. Tan et al, 2012;Cheng et al, 2016). For OBC5, zero-pressure was imposed at all the model outlets, representing the simplest outlet boundary condition.…”
Section: Discussionmentioning
confidence: 99%
“…While there is extensive research on coupled multidomain outflow boundary conditions that elucidate the explicit relationship between pressure and flow rate and its effect on the hemodynamics [30], literature on patient-specific inflow boundary conditions is scarce. To this end, studies by Kose et al [31], Kim et al [32], and Tan et al [33] demonstrated the use of PC-MRI-derived inlet velocity, corresponding to the patient-specific arterial geometry in rigid-wall fluid flow analyses.…”
Section: Effect Of Boundarymentioning
confidence: 99%
“…In the past few years, the role of computational modeling and simulations in design and verification of prosthetic heart valves is becoming more and more important (43). As a result, in vitro experimental testing such as the one presented in this study can be used to validate and verify the computational simulations (46)(47)(48)(49). As a result, in vitro experimental testing such as the one presented in this study can be used to validate and verify the computational simulations (46)(47)(48)(49).…”
Section: Discussionmentioning
confidence: 98%
“…The U.S. Food and Drug Administration (FDA) and EU Medical Device Regulatory System are major driving forces behind the trend (44,45). As a result, in vitro experimental testing such as the one presented in this study can be used to validate and verify the computational simulations (46)(47)(48)(49). A combined experimental and computational approach should be considered to shed light on the flow-mediated mechanisms of thrombosis in bioprosthetic aortic valves.…”
Section: Fluid Dynamic Characterization Of Transcatheter Aortic Valvesmentioning
confidence: 97%